Utilization of municipal solid waste compost for the improvement of microbial biomass, n-mineralization and fertility of soil under maize crop - Bibi, Hamida; Basit, Abdul; Shams, Dilawar Farhan; Khan, Muhammad Zafarullah; Iqbal, Mudassar; Ullah, Sajid (Applied Research in Science and Technology, 2022)
The experiment was conducted to assess the influence of municipal solid waste compost on microbial activity of soil after harvesting of maize crop and to determine the effect of municipal solid waste compost on N mineralization. A field experiment to test the effect of solid waste compost on fertility, microbial biomass and nitrogen (N) mineralization was conducted at Agriculture Research Institute Tarnab, Peshawar during spring 2017. A maize crop was selected as test crop for this experiment. The experiment was carried out in a Randomized Complete Block (RCBD) design with three replications. Maize variety (Azam) was sown in March 2017. Plot size was 5 × 3 m. Municipal solid waste compost was applied as treatment in each plot with different rates. The data showed maximum N mineralization (7.6 µg g-1 soil) at the treatment T2 where only NPK dose was applied while minimum N was mineralized at treatment T1 control where no NPK and MSW compost was applied, Then the application of MSW compost influenced N mineralization at large extent (6.4 µg g-1 soil) in treatment T4 where MSW compost was applied at 12 t ha-1 followed by the treatment T6 (6.1 µg g-1 soil) where MSW compost was applied at 24 t ha-1. Applying MSW compost influence microbial activities and increase soil organic carbon.